2011
DOI: 10.5251/ajbms.2011.1.1.8.16
|View full text |Cite
|
Sign up to set email alerts
|

Identification of molecular markers for Sw-5 gene of tomato spotted wilt virus resistance

Abstract: Tomato spotted wilt virus (TSWV) is one of the most destructive viral diseases that threaten worldwide tomato (Solanuum lycopersicum L. syn Lycopersicon esculentum Mill.) production. Use of host resistance appears to be the best way to control the disease. Marker assisted selection (MAS) has become very important and useful in the selection of TSWV resistance genes. The objective of this research was to identify Sw-5 gene-specific PCR-based molecular markers and gene-derived single nucleotide polymorphism (SNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 31 publications
(28 reference statements)
1
19
0
Order By: Relevance
“…Except for 'TY sense Q' and 'Titichal' that were already described by the provider to carry resistance to TSWV, 'Savera', 'TY tiny', 'Daylose' and 'Shinheuksu' were newly identified as cultivars carrying resistance to TSWV in this study. Previously, Shi et al (2011) also screened 14 tomato accessions and 10 commercial tomato cultivars for TSWVresistance and found that only three commercial cultivars ('Talladega', 'Sophya', and 'BHN-444') and one accession (LA3667) carried the Sw-5b allele for resistance to TSWV as shown in the Stevens cultivar, the original source of the Sw-5b allele for resistance to TSWV. In this study, completely different commercial cultivars from what Shi et al (2011) used were screened, and only six of them were determined to be TSWV-resistant.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Except for 'TY sense Q' and 'Titichal' that were already described by the provider to carry resistance to TSWV, 'Savera', 'TY tiny', 'Daylose' and 'Shinheuksu' were newly identified as cultivars carrying resistance to TSWV in this study. Previously, Shi et al (2011) also screened 14 tomato accessions and 10 commercial tomato cultivars for TSWVresistance and found that only three commercial cultivars ('Talladega', 'Sophya', and 'BHN-444') and one accession (LA3667) carried the Sw-5b allele for resistance to TSWV as shown in the Stevens cultivar, the original source of the Sw-5b allele for resistance to TSWV. In this study, completely different commercial cultivars from what Shi et al (2011) used were screened, and only six of them were determined to be TSWV-resistant.…”
Section: Resultsmentioning
confidence: 99%
“…The dominant PCR marker specific to Sw-5b with the primer pair Sw5b-f2/Sw5b-r2 (Table 2) was previously reported (Shi et al, 2011). Collected tomato cultivars were screened by PCR with this primer pair, including the TSWVsusceptible cultivars, Moneymaker and M82.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations